A comparison of the EU regulatory approach to directed mutagenesis with that of other jurisdictions, consequences for international trade and potential steps forward. Issue 4 (16th January 2019) - Eriksson, Dennis; Kershen, Drew; Nepomuceno, Alexandre; Pogson, Barry J.; Prieto, Humberto; Purnhagen, Kai; Smyth, Stuart; Wesseler, Justus; Whelan, Agustina
Summary: A special regulatory regime applies to products of recombinant nucleic acid modifications. A ruling from the European Court of Justice has interpreted this regulatory regime in a way that it also applies to emerging mutagenesis techniques. Elsewhere regulatory progress is also ongoing. In 2015, Argentina launched a regulatory framework, followed by Chile in 2017 and recently Brazil and Colombia. In March 2018, the USDA announced that it will not regulate genome‐edited plants differently if they could have also been developed through traditional breeding. Canada has an altogether different approach with their Plants with Novel Traits regulations. Australia is currently reviewing its Gene Technology Act. This article illustrates the deviation of the European Union's (EU's) approach from the one of most of the other countries studied here. Whereas the EU does not implement a case‐by‐case approach, this approach is taken by several other jurisdictions. Also, the EU court ruling adheres to a process‐based approach while most other countries have a stronger emphasis on the regulation of the resulting product. It is concluded that, unless a functioning identity preservation system for products of directed mutagenesis can be established, the deviation results in a risk of asynchronous approvals and disruptions in international trade.